2017
DOI: 10.1016/j.jtcvs.2016.07.080
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term durability of the Trifecta bioprosthesis for aortic valve replacement

Abstract: The Trifecta bioprosthesis is a reliable device for AVR. We confirm excellent immediate hemodynamic properties and a very low rate of patient-prosthesis mismatch. The absolute number of SVD cases observed remains limited; nevertheless, their timing, pathological characteristics, and clinical presentation mandate continued follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 27 publications
6
38
0
Order By: Relevance
“…Mortality at 30 days ranged from 1.5% to 3.8% in other Trifecta series (6,28). Our cohort presented a higher 30-day mortality rate (5.4%).…”
Section: Discussionmentioning
confidence: 49%
“…Mortality at 30 days ranged from 1.5% to 3.8% in other Trifecta series (6,28). Our cohort presented a higher 30-day mortality rate (5.4%).…”
Section: Discussionmentioning
confidence: 49%
“…The assumption is that valves made from bovine pericardium are superior to those made from porcine valves because of their improved hemodynamic characteristics; newer bioprostheses are mostly made from bovine pericardium (11). In smaller studies, such valves from bovine pericardium, such as the Trifecta valve, were again found to have better hemodynamic characteristics, with lower gradients and larger valve orifice areas (12)(13)(14).…”
Section: Materials and Evidence Of Durabilitymentioning
confidence: 99%
“…This new valve allows easier suturing and better placement in the native annulus, with a modified holder to facilitate parachuting and seating to minimize distortion to the stent and leaflets. 12 In this issue of JTCVS Techniques, Thocuta and colleagues 13 reported an unexpected early failure of the refined Trifecta GT that presented as newly diagnosed severe aortic insufficiency associated with a detached cusp at the stent post between the noncoronary and the right coronary cusps. 13 Noncalcified leaflet tears at the stent post or at the bottom of the leaflet without significant leaflet calcification are rather typical for Trifecta valves, whereas slow progress of calcification has been the primary cause of structural valve deterioration (SVD) in other types of bioprosthetic valves.…”
mentioning
confidence: 99%
“…13 Noncalcified leaflet tears at the stent post or at the bottom of the leaflet without significant leaflet calcification are rather typical for Trifecta valves, whereas slow progress of calcification has been the primary cause of structural valve deterioration (SVD) in other types of bioprosthetic valves. 12 Given the characteristics and timing of the SVD in the newer Trifecta GT, hemodynamic or mechanical stress on the externally mounted leaflet of the valve may contribute to the incidence of SVD, as has been seen among other externally mounted leaflet valves, including the Ionescu-Shiley valves in the 1980s, 14,15 and the recentgeneration Mitroflow valves in the 2000s. 16 Trifecta valves provided excellent early-to mid-term hemodynamic performance and a very low rate of PPM up to 6 or 7 years after surgery.…”
mentioning
confidence: 99%
See 1 more Smart Citation